1987
DOI: 10.1128/mcb.7.12.4225
|View full text |Cite
|
Sign up to set email alerts
|

Replication and segregation of plasmids containing cis-acting regulatory sites of silent mating-type genes in Saccharomyces cerevisiae are controlled by the SIR genes.

Abstract: In Saccharomyces cerevisiae, two cis-acting regulatory sites called E and I flank the silent mating-type gene, HMRa, and mediate SIR-dependent transcriptional repression of the al-a2 promoters. It has been shown previously that the E and I sites have plasmid replicator (ARS) activity. We show in this report that the ARS activity of the E and I sites is governed by the SIR genotype of the cell. In wild-type cells, a plasmid carrying the E site from HMRa (HMR E) in the vector YIp5 exhibited very high mitotic sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
87
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 41 publications
1
87
0
Order By: Relevance
“…All other plasmids used for strain construction have been described previously (Ivy et al 1986;Kimmerly and Rine 1987;Gottschling et al 1990;Aparicio et al 1991 ).…”
Section: Genes and Developmentmentioning
confidence: 99%
“…All other plasmids used for strain construction have been described previously (Ivy et al 1986;Kimmerly and Rine 1987;Gottschling et al 1990;Aparicio et al 1991 ).…”
Section: Genes and Developmentmentioning
confidence: 99%
“…This step was taken to minimize the SIR-dependent centromeric and ARS activities of the HMR silencers, E and I (9,34), in an attempt to optimize the probability of chromosomal integration. We found that gene transplacement was greatly facilitated in a sir4 background; in SIR' recipient cells, uracil prototrophs invariably harbored the HMR/ HSP82 fragments as multicopy episomes.…”
mentioning
confidence: 99%
“…One class of mutations affect segregation when the plasmid contains the HMRE ARS from the silencer of mating type information on the right arm of chromosome III (13). In wild-type strains, plasmids with the HMRE ARS are comparatively stable because they segregate randomly.…”
Section: Arsmentioning
confidence: 99%